Cross-coupled fuzzy logic sliding mode control of dual-driving feed system. (February 2018) - Lu, Hong; Fan, Wei; Zhang, Yongquan; Ling, He; Wang, Shaojun; Alghannam, Essa; Duan, Meng
Dual-driving systems have been widely adopted in advanced manufacturing machine. Synchronization of the dual-servo systems is crucial for tracking reference trajectories. This article proposes a novel cross-coupled fuzzy logic sliding mode control for the synchronous control of dual-driving feed system. The dynamic model of dual-driving system has been established and the individual proportional–proportional–integral controller is built based on the dynamic model. To increase the synchronous performance, a cross-coupled sliding mode controller is provided based on dual-driving system model. In addition, a continuous saturation function is adopted to reduce chattering. Lyapunov stability criterion is used to analyze the stability of the cross-coupled sliding mode control. Moreover, a fuzzy logic saturation gain control approach is proposed to overcome the low robustness and poor dynamic synchronous performance in the normal cross-coupled control scheme. The adaptive saturation function is designed to eliminate synchronous deviation caused by the process of two axes following each other. Finally, an industrial application of dual-driving system is utilized to prove the effectiveness of the proposed scheme. The proposed cross-coupled fuzzy logic sliding mode control scheme has been effectively demonstrated to improve synchronous performance and tracking accuracy.